Toward understanding the contribution of waterbodies to the methane emissions of a permafrost landscape on a regional scale—A case study from the Mackenzie Delta, Canada. (24th May 2018) - Kohnert, Katrin; Juhls, Bennet; Muster, Sina; Antonova, Sofia; Serafimovich, Andrei; Metzger, Stefan; Hartmann, Jörg; Sachs, Torsten
Abstract: Waterbodies in the arctic permafrost zone are considered a major source of the greenhouse gas methane (CH4 ) in addition to CH4 emissions from arctic wetlands. However, the spatio‐temporal variability of CH4 fluxes from waterbodies complicates spatial extrapolation of CH4 measurements from single waterbodies. Therefore, their contribution to the CH4 budget of the arctic permafrost zone is not yet well understood. Using the example of two study areas of 1, 000 km² each in the Mackenzie Delta, Canada, we approach this issue (i) by analyzing correlations on the landscape scale between numerous waterbodies and CH4 fluxes and (ii) by analyzing the influence of the spatial resolution of CH4 flux data on the detected relationships. A CH4 flux map with a resolution of 100 m was derived from two aircraft eddy‐covariance campaigns in the summers of 2012 and 2013. We combined the CH4 flux map with high spatial resolution (2.5 m) waterbody maps from the Permafrost Region Pond and Lake Database and classified the waterbody depth based on Sentinel‐1 SAR backscatter data. Subsequently, we reduced the resolution of the CH4 flux map to analyze if different spatial resolutions of CH4 flux data affected the detectability of relationships between waterbody coverage, number, depth, or size and the CH4 flux. We did not find consistent correlations between waterbody characteristics and the CH4 flux in the two study areas across the different resolutions. Our results indicate that waterbodies in permafrost landscapes, even if they seem to be emission hot spots on an individual basis or contain zones of above average emissions, do currently not necessarily translate into significant CH4 emission hot spots on a regional scale, but their role might change in a warmer climate. Abstract : Waterbodies in arctic permafrost regions are considered to be important sources of the greenhouse gas methane. To study the contribution of methane emissions from waterbodies on a regional scale, we combined aircraft measurements of methane and remote sensing products for waterbody characterization. Our results indicate that waterbodies in permafrost landscapes, even if they seem to be emission hot spots on an individual basis, do currently not necessarily translate into significant methane emission hot spots on a regional scale